Bibliography about Islamic Studies - Abdel-Bagi, Ala-Addin Hassan (Tafakkur; Vol 5 No 1 (2003), 2018)
Alfarougi Library of Imam contains many foreign references and Journals of Islamic Studies .The importance of these references and Journals gives us the pleasure to write this bibliography for the sake of the library user